High erythroferrone expression in CD71+ erythroid progenitors predicts superior survival in myelodysplastic syndromes - Riabov, Vladimir; Mossner, Maximilian; Roth, Alexandra; Jann, Johann-Christoph; Streuer, Alexander; Schmitt, Nanni; Knaflic, Antje; Nowak, Verena; Weimer, Nadine; Obländer, Julia; Palme, Iris; Schumann, Christiane; et al. (British journal of haematology, 2021)
Ineffective erythropoiesis and iron overload are common in myelodysplastic syndromes (MDS). Erythroferrone (ERFE) and growth/differentiation factor 15 (GDF15) are two regulators of iron homeostasis produced by erythroid progenitors. Elevated systemic levels of ERFE and GDF15 in MDS are associated with dysregulated iron metabolism and iron overload, which is especially pronounced in MDS with SF3B1 gene mutations. However, the role of ERFE and GDF15 in MDS pathogenesis and their influence on disease progression are largely unknown. Here, we analyzed the expression of ERFE and GDF15 in CD71+ erythroid progenitors of n = 111 MDS patients and assessed their effects on patient survival. The expression of ERFE and GDF15 in MDS was highly aberrant. Unexpectedly, ERFE expression in erythroprogenitors was highly relevant for MDS prognosis and independent of International Prognostic Scoring System (IPSS) stratification. Although ERFE expression was increased in patients with SF3B1 mutations, it predicted overall survival (OS) in both the SF3B1wt and SF3B1mut subgroups. Of note, ERFE overexpression predicted superior OS in the IPSS low/Int-1 subgroup and in patients with normal karyotype. Similar observations were made for GDF15, albeit not reaching statistical significance. In summary, our results revealed a strong association between ERFE expression and MDS outcome, suggesting a possible involvement of ERFE in molecular MDS pathogenesis.
Im Titel ist "+" hochgestellt
Gesehen am 27.07.2021